Academic literacy among the university students in Mexico and Spain: A holistic perspective - Castillo-Martínez, Isolda Margarita; Cerros Regalado, Cynthia Patricia; Glasserman-Morales, Leonardo David; Ramírez-Montoya, María Soledad (Frontiers in Psychology, 2023)
Nowadays, young people have access to a large amount of information, so it is important that they have the ability to critically analyze the texts they are exposed to in order to choose those that are really useful for their training or research process, as well as to have the necessary skills to interact efficiently with the texts, especially with those specialized documents corresponding to their area of study. In this sense, this article aims to identify how cognitive, emotional, attitudinal, digital and personality aspects influence the development of academic literacy skills in university students. A Mixed Method research was conducted, in which quantitative instruments were applied and analyzed: a Likert scale questionnaire to measure the perceived level of mastery of academic literacy skills, which was applied to a sample of 595 students from higher education institutions in Mexico and Spain. In addition, a test was applied to identify personality type. For the qualitative part, the case study was chosen and the qualitative instruments applied were: interviews with a teacher and a student and a focus group with five students. The findings identified were: a) The cognitive aspect of academic literacy is the one with the lowest perceived mastery by students, b) Having a positive attitude favors the development of academic literacy, c) By knowing the aspects of their personality that can favor the development of academic literacy, students can seek strategies to improve that competency, d) The emotional part has repercussions in the process of developing the competence of academic literacy, e) Students prefer to interact with texts in digital spaces and therefore must learn to interact critically in virtual environments, f) Mexican students perceive themselves to have a higher level of mastery of the academic literacy competency than Spanish students, e) The literature review and the Mixed Methods study allowed identifying the relevance of approaching academic literacy in university environments in a holistic manner through the analysis of the influence of cognitive, attitudinal, emotional, digital and personality aspects.